The Irish single-currency debate of the 1990s in retrospect - Frank Barry (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2017)
Ireland was one of the initial EU member states to move to currency union as of January 1st 1999. The single-currency project, and Ireland's participation in it, had been vigorously debated within the Irish economics community in the 1990s. The paper reviews this debate with three particular questions in mind. To what extent was it recognised that membership might increase Ireland's vulnerability to external shocks? Would membership inhibit or facilitate an appropriate response, and were the implications of membership for the appropriate conduct of economic policy correctly identified? The paper also briefly reviews current thinking on necessary reforms to eurozone structures. It ends by considering the counter-factual - what exchange rate regime would Ireland have adopted if it had not joined the euro, and what might the consequences have been? - and offers a retrospective assessment of the debate that took place prior to membership.
Keywords: 330; Monetary union; single currency; Ireland